1996
DOI: 10.1080/135467896394519
|View full text |Cite
|
Sign up to set email alerts
|

Self-insight, Other-insight, and Their Relation to Interpersonal Conflict

Abstract: The pessimistic conclusion that people have relatively poor insight into the weighting schemes they use when they make holistic judgements has been generally accepted among judgement researchers (e.g. Arkes, 1981; Balke, Hammond, & Meyer, 1973, Brehmer, 1984. The empirical research that supported this generalisation rested on indices of self-insight that were produced directly by the subjects. It was often the case that subjects were unable to correctly name even the single most important factor influencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Like Reilly andDoherty (1989, 1992) and Reilly (1996), we found that participants were able to select their policies at rates signi®cantly greater than chance. There was no dierence in policy-selection performance between stated and tacit policies.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Like Reilly andDoherty (1989, 1992) and Reilly (1996), we found that participants were able to select their policies at rates signi®cantly greater than chance. There was no dierence in policy-selection performance between stated and tacit policies.…”
Section: Discussionmentioning
confidence: 59%
“…Of course, each participant's subjective linear model is inferior to the objective model used in a judgement analysis in describing behaviour: the objective weights are obtained from the line of best ®t (Reilly, 1996;Reilly and Doherty, 1992;Slovic and Lichtenstein, 1971). But objective models are also superior when using crossvalidation, i.e.…”
Section: Comparison With the ®T Of Other Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the hundreds of published studies based on the Functional Theory of Cognition [9], people are not asked directly and explicitly to place values on individual things or pieces of information, for people's self-insight is often limited [10]. Instead, these values and the rules used to integrate them are inferred from the judgments the people make about a set of different combinations of the information.…”
Section: Introductionmentioning
confidence: 98%